Association between early history of asthma and COPD diagnosis in later life: a systematic review and meta-analysis. (1st October 2018) - Asamoah-Boaheng, Michael; Acheampong, Lily; Tenkorang, Eric Y; Farrell, Jamie; Oyet, Alwell; Midodzi, William K
Abstract: Background: Whereas most studies have reported prior history/diagnosis of asthma as an independent risk factor for chronic obstructive pulmonary disease (COPD) development in later life, no systematic review and meta-analysis has been conducted to synthesize these observational studies. The aim of this review is to investigate associations between prior history of asthma and later development of COPD. Methods: We conducted a comprehensive search in PubMed, CINAHL and EMBASE for studies related to prior history of asthma and COPD diagnosis. Articles were screened for relevance by two independent reviewers. Methodological quality was independently assessed and data extracted for qualitative and quantitative review. We explored heterogeneity and performed a publication bias check. Results: From the 1260 articles retrieved, 9 were included in the qualitative review and 7 in the meta-analysis. History of asthma was associated with developing COPD in later life (Inverse Variance Random-effects model, odds ratio: 7.87, 95% confidence interval: 5.40–11.45, p < 0.00001). Conclusions: Studies with high methodological quality provided sufficient evidence to suggest that individuals with previous history of asthma have an increasing likelihood of developing COPD in later life.